Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Sub Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia - Ebin Franico; Lidya Martha (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
This study aims to analyze the effect of financial performance, proxied by liquidity, leverage, and profitability, on firm value in plantation sub-sector companies listed on the Indonesia Stock Exchange. Firm value is measured using Price to Book Value (PBV). This research employs a quantitative approach with a causal associative method. The data used are secondary data obtained from financial statements, with data analysis techniques using multiple linear regression. The results indicate that liquidity does not have an effect on firm value. However, leverage and profitability both have a positive effect on firm value, both partially and simultaneously. These findings imply that financial performance plays an important role in influencing investor perceptions of firm value. Investors tend to value companies with better leverage and profitability ratios as they signal better financial health and future growth potential. The study highlights the significance of understanding the components of financial performance and their impact on firm value, offering valuable insights for stakeholders in making informed investment decisions. Furthermore, the study suggests that improving financial performance, particularly in leverage and profitability, could enhance firm value and attract more investment.